2014
DOI: 10.1007/s00056-014-0243-7
|View full text |Cite
|
Sign up to set email alerts
|

Controlling pain during orthodontic fixed appliance therapy with non-steroidal anti-inflammatory drugs (NSAID): a randomized, double-blinded, placebo-controlled study

Abstract: Etoricoxib 60 mg is highly efficacious for controlling pain during fixed orthodontic appliance therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
3
14
0
1
Order By: Relevance
“…The other drugs tested were etoricoxib, lumiracoxib, meloxicam, piroxicam, and tenoxicam. Gupta et al 20 compared the effects of administration of paracetamol, etoricoxib, and placebo 1 hour before and 3 days after the first orthodontic arch was installed. They concluded that etoricoxib was more effective in reducing pain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other drugs tested were etoricoxib, lumiracoxib, meloxicam, piroxicam, and tenoxicam. Gupta et al 20 compared the effects of administration of paracetamol, etoricoxib, and placebo 1 hour before and 3 days after the first orthodontic arch was installed. They concluded that etoricoxib was more effective in reducing pain.…”
Section: Resultsmentioning
confidence: 99%
“…Patel et al 11 observed that ibuprofen had a greater effect on orthodontic pain compared to naproxen sodium, in contrast to the study by Polat et al, 12 who observed that naproxen sodium was more effective than ibuprofen. The efficacies of aspirin, 13 , 14 etoricoxib, 20 meloxicam, 22 piroxicam, 23 and tenoxicam 24 were also evaluated; these drugs were found to be effective in reducing orthodontic pain. Lumiracoxib, however, was not effective.…”
Section: Discussionmentioning
confidence: 99%
“…Further, SBI also showed a significant difference at the first and third months than that at baseline, but no significant difference were found between adult and children subgroups as well as between different time points of the first and third month. This might indicated that inflammatory reaction might be occurred in the initial stage of orthodontic treatment [33], but then stabilized and without persistent deterioration during the following periods, more investigation should be conducted to confirm such speculation with the detection of inflammatory related parameters. Sharma NC et al mentioned in their study that both PLI and SBI were decreased following the treatment process for children applied fixed orthodontic appliances, which was suggested to have beneficial results for the reduction of plaques and bleeding [34].…”
Section: Discussionmentioning
confidence: 99%
“…Orthodontic pain is inevitably an adverse effect of orthodontic treatment. To date, numerous modalities have been invented to alleviate orthodontic pain in clinical practice, including pharmacological approaches, 113 , 114 , 115 mechanical approaches, 116 , 117 laser irradiation therapy 68 , 69 and behavioural approaches. 14 , 81 Furthermore, a novel modality for pain relief—gene therapy—is gaining popularity and may be promising in future pain relief among orthodontic patients.…”
Section: Management Of Orthodontic Painmentioning
confidence: 99%